The health-related impacts and costs of violence against women and girls on survivors, households and communities in Ghana - Gina Alvarado; Ama P. Fenny; Samuel Dakey; Jennifer L. Mueller; Lila O'Brien-Milne; Aba O. Crentsil; Nata Duvvury; Stacey Scriver; Chloe Schwenke (AOSIS, 2018)
Past research on violence in Ghana primarily discusses domestic violence and some types of sexual violence, but lacks a comprehensive analysis of violence against women and girls (VAWG) and its wider costs and impacts. Our study on the social costs of VAWG is a unique contribution, which aims to fill that gap. Through indepth interviews (IDIs) and focus group discussions (FGDs) with adult women and men, we explored the health impact of VAWG and the resulting social and economic consequences on survivors, their families and their communities. The research, which took place in the Eastern, Central, and Greater Accra regions of Ghana, points to several physical and mental health outcomes among survivors including physical injuries and disability, as well as impacts on mental health such as anxiety and suicidal ideation. Many VAWG survivors also experience stigma and social isolation. Our findings also reveal that survivors' families can bear various social and economic costs. Lack of public and private service provision and shelters for survivors heighten these impacts. Without institutional support for survivors, families and communities absorb these costs of VAWG.